Consolidation of vacancy by transplanting old china hybrid tea (Camellia sinensis) in hilly areas - Jain, N K; Chacrabarty, D N; Singh, R D; Sud, R K; Tamang, M B (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during 1987-89 to study the Survival and growth of century old china hybrid tea [Camellia sinensis)(L.) O. Kuntze] after transplanting in different months by using different lengths of root, with and without three 45 cm tall breathers. The survival was highest (78-97%) when the plants were shifted during December-August except June; bush yield was the highest when transplanted during February-May (196.9-294.5 kg made-tea/ha); and number of primaries were maximum when transplanted during November-March (0.085-0.115/cm2 ). Root lengths of < 35 cm adversely affected the recovery (51.7-75.7%), shoot growth (height 14.3--16.7 cm) and crop yield (44.1-100.4 kg made-tea/ha). Leaving breathers on transplants had little influence on survival or shoot growth of the plant.